Towards a hybridization of vocational and academic qualification paths? Evidence from companies' recruitment and training strategies in selected industries - Mottweiler, Hannelore [Verfasser]; Annen, Silvia [Verfasser] (My University, 2020)
"In Germany, current scientific debates on the relationship between the vocational and the higher education systems discuss the end of a clear distinction between both systems. On the one hand, this is reflected by an increasing permeability between vocational and academic qualification pathways (Wolter & Kerst, 2015). On the other hand, researchers conclude growing areas of overlap between vocational and higher education (e. g. Severing & Teichler, 2013) as well as an increase of hybrid models combining vocational and academic characteristics (e.g. Euler, 2017). Against this background, this paper seeks to provide a comprehensive analysis of the recruitment and training strategies of companies in relation to selected educational models. In doing so, the following qualification strategies used by companies in four different industries are compared: dual study programs, special 'fast track' vocational training programs combining initial and further vocational training certificates and trainee programs for externally recruited university graduates. The results allow for a substantiated evaluation of the use of certain recruitment strategies by companies and a differentiated view of the relevant context factors." (authors' abstract; BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 3.2 Unternehmen und Behörden; S 5.3 Personalentwicklung; Berufsausbildung; Hochschulbildung; Durchlässigkeit im Bildungssystem; Verzahnung beruflicher und hochschulischer Bildung; Betrieb; Personalgewinnung